Transformações pelo caminho: a última narrativa - Santana, Danilo (Universidade Federal de São Carlos, 2019)
Reflective Narrative about the experiences acquired by the student during the undergraduate medical course, from 2014 to 2019, divided into cycles, consisting of two years, as well is the Medical course at the Federal University of São Carlos, organized according to the progression in the domain of knowledge, in each area of competence, considering increasing degrees of autonomy.
Transformations through the path: the last narrative
Keywords: Educação médica; Processo de ensino-aprendizagem; Graduação médica; Formação profissional; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM